The human capital theory as the basis for development of integrated reporting - Renkas, Yurij (SPC Journal of Social Sciences, 2020)
The article presents the method of preparing a report on the level of payment of human capital of the employees in the light of the concept of integrated reporting. For this purpose, an original model of measuring the value of human capital of employees and the method of determin-ing the size of remuneration were introduced.Â Â